A pedagogia histórico-crítica no estágio supervisionado em espaços escolares: limites e possibilidades para a prática pedagógica na educação física - FREITAS, Rhenan Ferreira de (2022)
The present work has as a question How do Physical Education classes in Supervised Stage I and II / UFPA materialize, based on the theoretical framework of Historical-Critical Pedagogy? And its objective is to analyze the materialization of Physical Education classes in Supervised Internship activities by the theoretical framework of Historical-Critical Pedagogy. The methodological course traced from the approximation with the dialectical historical materialist method. Our research was developed from a field research, whose locus was Stages I and II, the subjects were characterized as students / trainees of the Physical Education / UFPA course of the fifth and sixth semester that used the theoretical and methodological framework of the Historical-Critical Pedagogy in ES classes. The results show that the materiality came from the assimilation - not in its entirety - of the referential by most students. Methodologically, there was more accumulation on questions related to the structuring of the classes that contributed to its better development, but that there is a need for further study by the students about this referential. It is concluded at the end of our research that the Physical Education classes in Supervised Stage I and II / UFPA materialize from the partial assimilation of the PHC framework, because most students were able to understand it, with its theoretical and methodological foundations. teaching, not in its entirety, but in specific questions to teach in favor of the materialization of historically systematized knowledge.